2018
DOI: 10.1002/npr2.12006
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive behavioral analysis of tryptophan 2,3‐dioxygenase (Tdo2) knockout mice

Abstract: Aims: Tryptophan 2,3-dioxygenase (TDO2) is an initial rate-limiting enzyme of the kynurenine (Kyn) pathway in tryptophan (Trp) metabolism. The Trp-degrading enzymes, TDO2 and indoleamine 2,3-dioxygenase, are activated by stress and/or inflammation. Dysregulation of Trp metabolism, which causes shifts in the balance between Kyn and serotonin (5-HT) pathways, is associated with psychiatric and neurological disorders. In genetic studies, single-nucleotide polymorphisms in the TDO2 gene were shown to be involved i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…In this report, we utilized a comprehensive set of well-defined behavioral tests [31][32][33][34][35][36][37][38] and investigated behavioral phenotypes including the sensorimotor functions and the cognitive functions of the Syngap1 −/+ mice generated by Komiyama et al on a C57BL/6J genetic background.…”
Section: Introductionmentioning
confidence: 99%
“…In this report, we utilized a comprehensive set of well-defined behavioral tests [31][32][33][34][35][36][37][38] and investigated behavioral phenotypes including the sensorimotor functions and the cognitive functions of the Syngap1 −/+ mice generated by Komiyama et al on a C57BL/6J genetic background.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, decreased kynurenine metabolites and increased Trp and 5-HT concentrations can lead to a reduction of anxiety in the hippocampus and midbrain for improving search activity and cognitive ability. 32 …”
Section: Discussionmentioning
confidence: 99%
“…Normally, the oxidizing ability of TDO2, that is its ability to metabolize tryptophan, is approximately threefold greater than that of IDO1 . Tdo2 deletion disturbs the KP and causes more behavioral alterations, such as lower anxiety‐like behavior and higher locomotor activity under basal conditions, than Ido1 deletion . IDO1 activity is quite low in the absence of immune stimuli, which may underlie the lack of an obvious behavioral phenotype in Ido1 KO mice.…”
Section: Discussionmentioning
confidence: 99%
“…The perturbation of IDO1 or TDO2 activity, which causes KP imbalance, is also reported to be associated with psychiatric and neurological disorders . In our previous study, we conducted a comprehensive battery of behavioral tests with Tdo2 KO mice, which showed lower anxiety‐like behavior, higher locomotor activity, and abnormal gait patterns than the controls . It has been reported that WT mice under inflammatory conditions show increased anxiety‐like behavior in open field and light/dark transition tests, increased depressive‐like behavior on forced swim and tail suspension tests, and decreased novel object recognition, whereas Ido1 KO mice do not exhibit these behaviors .…”
Section: Introductionmentioning
confidence: 99%